Synthesis of Some New 2-[3-(2-chloro quinolinyl)]-3-aryl-4-thiazolidinones as Potent Antibacterial Agents - Selvi, G.; Rajendran, S.P. (Asian Journal of Chemistry, 2016)
4-Thiazolidinone derivatives were prepared by the cyclocondensation of mercaptoacetic acid with quinoline aldimines which in turn were obtained by reacting 2-chloro-3-formylbenzo (h) quinoline and 2,6-dichloro-3-formyl-4-phenylquinoline with various substituted amines. The compounds have been characterized by spectral data. Selected compounds were screened for their antibacterial activity.